Slovak Republic : Staff Report for the 2004 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This 2004 Article IV Consultation highlights that Slovakia's economic performance has improved since the 2003 Article IV Consultation. Output has expanded strongly, and fiscal and external balances have narrowed substantially in recent years. These developments were assisted by large foreign direct investments and an improved business climate following important reforms-including to taxation, welfare, pensions, healthcare, and the labor market-that are supporting convergence to western European income levels. Economic activity was entirely export driven in 2003; real GDP increased by 4.5 percent despite a contraction in domestic demand.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet